Pengaruh Motivasi Dan Kompensasi Terhadap Kepuasan Kerja Karyawan Pada PT. Anugrah Karya Aslindo Pekanbaru - Yulita, Rahma; Firmansyah, Firmansyah (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study was carried out, among others, to find out the extent of the influence of motivation on job satisfaction at PT. Anugrah Karya Aslindo Pekanbaru, to find out the extent of the influence of compensation on job satisfaction at PT. Anugrah Karya Aslindo Pekanbaru, and to find out the extent of the influence of motivation and compensation on job satisfaction at PT. Anugrah Karya Aslindo Pekanbaru. The population of the research object is 50 employees with a sample withdrawal technique using a census, while the research data analysis technique used by the researcher uses multiple regression analysis. So the result of the conclusion that can be drawn from this study is that motivation has a significant effect on employee job satisfaction at PT. Anugrah Karya Aslindo Pekanbaru, compensation has a significant effect on employee job satisfaction at PT. Anugrah Karya Aslindo Pekanbaru, and motivation and compensation have a significant effect on job satisfaction.